Adsorption characteristics of toluene and trichloroethylene onto activated carbon fiber - Park, JW; Lee, YW; Choi, DK; Lee, SS (ELSEVIER SCIENCE INC, 2003)
The breakthrough curves of toluene and trichloroethylene onto activated carbon fiber in single and binary system were measured in an isothermal condition of 298 K. Experimental and theoretical breakthrough curves for pure component were reflected by the effects of operation variables such as partial pressure for adsorbate and interstitial bulk fluid velocities. Because of the adsorption affinity difference between toluene and trichloroethylene, roll-up phenomenon was observed in the breakthrough curve of trichloroethylene. Breakthrough curve analysis showed that the extended Langmuir equation could explain column dynamics with good accuracy. A dynamic model based on the linear driving force mass transfer model, which was suggested to represented column dynamics, showed that the prediction data results agreed remarkably with the experimental data.
Keywords: THERMAL REGENERATION; DICHLOROMETHANE; EQUILIBRIA; DIFFUSION; VAPORS; BEDS